IMPACT OF BODY MASS INDEX ON LEFT VENTRICULAR MASS - Rashid, Munir Ahmad; Qureshi, Bilal Ahsan; Ahmed, Nisar; Sherwani, Mubasher Ali (Journal of Ayub Medical College Abbottabad, 2014)
Background: Obesity is an independent factor implicated in left ventricular (LV) hypertrophy and increased left ventricular mass. Early detection of increased LV mass in obese patients has prognostic and therapeutic implications. Methods: This case series was carried out in Choudhry Pervaiz Ellahi Institute of Cardiology, Multan from March to August 2011. A total of 100 consecutive patients including male and female referred for transthoracic echocardiography were included in this study. Patient’s demographics were obtained using a questionnaire. Anthropometry (BMI) and two-dimensional echocardiography to calculate LV mass. Results: Echocardiograms of 100 patients showing mean age 42.42±6.04 years, with BMI of 28.42±5.52 and LV Mass of 136.05±29.117shown linear correlation between BMI and LV mass. Conclusion: In is concluded from the study thatLV mass increases with increasing BMI. Keyword: Echocardiography, Body mass index, LV mass